Pro-poor climate risk insurance: the role of community-based organisations (CBOs) - Denise Margaret Matias; Raúl Fernández; Marie-Lena Hutfils; Maik Winges (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
In the face of increasingly frequent extreme weather events, the need to manage climate risk becomes more urgent, especially for the most vulnerable countries and communities. With the aim of reducing vulnerability, climate risk transfer in the form of climate risk insurance (CRI) has been gaining attention in climate policy discussions. When properly designed, CRI acts as a safety net against climate change impacts by providing financial support after an extreme weather event. Two main types of insurance enable payouts: indemnity (traditional) insurance or predefined parameters (index-based) insurance. Individuals, groups, or even governments may take out policies with either type of insurance and receive payouts directly (insurer to beneficiary payout) or indirectly (insurer to aggregator to beneficiary payout). Direct insurance is usually implemented at the micro-level with individual policyholders. Indirect insurance is usually implemented through group contracts at the meso-level through risk aggregators and at the macro-level through the state. While promising, risk transfer in the form of CRI also has its share of challenges. Within the United Nations Framework Convention on Climate Change, the lack of accessibility and afford¬ability of CRI for poor and vulnerable groups have been identified as barriers to uptake. In light of climate justice, asking the poor and climate-vulnerable groups - most of whom do not contribute substantially to anthropogenic climate change - to solely carry the financial burden of risk transfer is anything but just. Employing a human rights-based approach to CRI may ensure that the resilience of poor and climate-vulnerable groups is enhanced in a climate-just manner. Indigenous peoples are some of the poorest and most climate vulnerable groups. Often marginalised, they rarely have access to social protection. The strong communal relationship of indigenous peoples facilitates their participation in community-based organisations (CBOs). CBOs are a suitable vehicle for meso-insurance, in which risk is aggregated and an insurance policy belongs to a group. In this way, CBOs can facilitate service provision that would otherwise be beyond the reach of individuals. Conclusions of this briefing paper draw on a conceptual analysis of meso-insurance and the results of field research conducted in March 2018 with indigenous Palaw'ans in the Philippines. We find that CRI needs to be attuned to the differential vulnerabilities and capacities of its beneficiaries. This is particularly true for poor and vulnerable people, for whom issues of accessibility and affordability need to be managed, and human rights and pro-poor approaches need to be ensured. In this context, meso-insurance is a promising approach when it provides accessibility and affordability and promotes a pro-poor and human rights-based approach of risk transfer by: Properly identifying and involving target beneficiaries and duty-bearers by employing pro-poor and human rights principles. Employing measures to improve the financial literacy of target beneficiaries. Designing insurance models from the bottom up.
Keywords: 330; Armut und Ungleichheit; Klimawandel